2020
DOI: 10.1186/s12882-020-01741-9
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota characteristics of Chinese patients with primary IgA nephropathy: a cross-sectional study

Abstract: Background: Growing evidence has shown that the gut-renal connection and gut microbiota dysbiosis play a critical role in immunoglobulin A nephropathy (IgAN). However, the fecal microbiome profile in Chinese patients with IgAN remains unknown. A cross-sectional study was designed for the first time to investigate the fecal microbiota compositions in patients with primary IgAN in China and to evaluate the relationship between the fecal microbiome and IgAN clinical presentation. Methods: Fecal samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 67 publications
9
79
0
Order By: Relevance
“…Twelve (12/25) studies analyzed the relatively distinct taxa at the phylum level ( Table S6 ), of which two studies (2/10) focused on ESRD [ 24 , 25 ]. Six (6/10) and three (3/10) studies demonstrated that Proteobacteria [ 24 , 25 , 27–29 , 33 ] and Fusobacteria [ 18 , 27 , 34 ] were more abundant, while two (2/10) studies [ 18 , 29 ] showed that the abundance of Synergistetes in patients with CKD was less than that in controls. The abundance of Firmicutes , Bacteroidetes , and Actinobacteria in patients with CKD was inconsistent when compared to controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve (12/25) studies analyzed the relatively distinct taxa at the phylum level ( Table S6 ), of which two studies (2/10) focused on ESRD [ 24 , 25 ]. Six (6/10) and three (3/10) studies demonstrated that Proteobacteria [ 24 , 25 , 27–29 , 33 ] and Fusobacteria [ 18 , 27 , 34 ] were more abundant, while two (2/10) studies [ 18 , 29 ] showed that the abundance of Synergistetes in patients with CKD was less than that in controls. The abundance of Firmicutes , Bacteroidetes , and Actinobacteria in patients with CKD was inconsistent when compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Of 12 studies, 10 studies were conducted in China, and two (2/10) studies focused on ESRD. Five (5/8), two (2/8), and two (2/8) studies demonstrated that Proteobacteria [ 20 , 27–29 , 33 ], Fusobacteria [ 18 , 27 ], and Bacteroidetes [ 17 , 33 ] were more abundant, while four (4/8) and two (2/8) studies revealed that Firmicutes [ 17 , 27 , 28 , 33 ] and Synergistetes [ 18 , 29 ] were less abundant in Chinese CKD patients compared with healthy controls, respectively. However, the two studies conducted in the US [ 34 ] and Italy [ 19 ] did not identify any taxa with the same alteration in CKD patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In supporting this, studies showed that the microbial characteristics among patients with IgAN and healthy controls were different. More specifically, higher percentages of the Ruminococcaceae , Lachnospiraceae , Eubacteriaceae, Streptococcaeae, Escherichia-Shigella , Hungatella , or Eggerthella genera/species could be observed in patients with IgAN 27 , 28 . Moreover, patients with IgAN presented significantly higher intestinal permeability, which was related to increased proteinuria, microhematuria, and serum levels of IgA when compared with healthy controls 14 .…”
Section: Immunoglobulin a (Iga)mentioning
confidence: 99%